Salmonella identified in pigs in Kenya and Malawi reveals the potential for zoonotic transmission in emerging pork markets - Wilson, C.N.; Pulford, C.V.; Akoko, James M.; Sepulveda, B.P.; Predeus, A.V.; Bevington, J.; Duncan, P.; Hall, N.; Wigley, P.; Feasey, N.; Pinchbeck, G.; Hinton, J.C.D.; et al. (Public Library of Science, 2020)
Salmonella is a major cause of foodborne disease globally. Pigs can carry and shed non-typhoidal Salmonella (NTS) asymptomatically, representing a significant reservoir for these pathogens. To investigate Salmonella carriage by African domestic pigs, faecal and mesenteric lymph node samples were taken at slaughter in Nairobi, Busia (Kenya) and Chikwawa (Malawi) between October 2016 and May 2017. Selective culture, antisera testing and whole genome sequencing were performed on samples from 647 pigs; the prevalence of NTS carriage was 12.7% in Busia, 9.1% in Nairobi and 24.6% in Chikwawa. Two isolates of S. Typhimurium ST313 were isolated, but were more closely related to ST313 isolates associated with gastroenteritis in the UK than bloodstream infection in Africa. The discovery of porcine NTS carriage in Kenya and Malawi reveals potential for zoonotic transmission of diarrhoeal strains to humans in these countries, but not for transmission of clades specifically associated with invasive NTS disease in Africa.